2014
DOI: 10.1063/1.4900843
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viscosity contrast on gravitationally unstable diffusive layers in porous media

Abstract: We investigate the effect of viscosity contrast on the stability of gravitationally unstable, diffusive layers in porous media. Our analysis helps evaluate experimental observations of various diffusive (boundary) layer models that are commonly used to study the sequestration of CO2 in brine aquifers. We evaluate the effect of viscosity contrast for two basic models that are characterized with respect to whether or not the interface between CO2 and brine is allowed to move. We find that diffusive layers are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 23 publications
5
56
0
Order By: Relevance
“…Daniel & Riaz 2014) to analyze the influence of viscosity contrast on the stability of a buoyantly unstable miscible layer. Two different cases are considered: (i) the upper fluid is more viscous than the lower one, and (ii) the lower fluid is more viscous than the upper one.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Daniel & Riaz 2014) to analyze the influence of viscosity contrast on the stability of a buoyantly unstable miscible layer. Two different cases are considered: (i) the upper fluid is more viscous than the lower one, and (ii) the lower fluid is more viscous than the upper one.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the temporal evolution of the growth rates obtained for different viscosity contrasts are visually almost indistinguishable. The physical explanation for a different onset time of instability in flow with or without viscosity contrast in buoyantly unstable miscible fluids can be presented in terms of the instantaneous vorticity perturbation field as discussed by Daniel & Riaz (2014). From figure 2(b) it is identified that for all time the most unstable wavenumbers are larger in the absence of the viscosity contrast compared to the situation when the viscosity of the two fluids are different.…”
Section: Effect Of Viscosity Contrast In the Absence Of Displacementmentioning
confidence: 95%
See 3 more Smart Citations